Economic damage and loss assessment on neighboring households from the 2022 Sitakunda fire event explosion shock waves - Asim Abrar; A. S. M. Maksud Kamal; S. M. Kamrul Hasan; Mahfuz Kabir (Discover Applied Sciences)
Abstract The 2022 Sitakunda fire event highlights the impact of high population density and insufficient safety measures on the severity of fire hazards, often resulting in significant loss of life. This study aimed to conduct a damage and loss assessment of the households present in the nearby neighborhoods in monetary terms due to shock waves emitted from the event explosions. Field assessments were conducted within a 2 km radius of the depot incident, collecting data on the types and monetary value of damaged items in each household, as well as income loss. Respondents also reported any recurring psychological impact due to the event. Results show that housings within 500 m of the event received significantly greater monetary damage than housings outside the 500 m radius. Damage types varied by housing structure, with Pucca houses experiencing more damage to windows and walls, while Kutcha houses suffering greater damage to roofs. The damage and loss characteristics showcase the expected total and type of damage that can be observed among semi-built and low-storied built structures from shock waves emitted from fire explosions of such caliber. These findings highlight specific vulnerabilities in households affected by such hazards and can inform government and policymakers in developing effective recovery, social protection, and rehabilitation plans to enhance community resilience and mitigate risks.